2011
DOI: 10.2478/10004-1254-62-2011-2128
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Lower Drava River Water Quality Parameters Over 24 Years

Abstract: The goal of this study was to analyse 13 physico-chemical and microbiological parameters of the Drava River water at three sampling sites in the lower Drava region (eastern Croatia) over two distinct periods: the pre-war period between 1985 and 1992 and the post-war period between 1993 and 2008. Over both periods, most parameters kept within the tolerable water quality limits, while NO 3 -N, NH 4 -N and BOD 5 were higher. The lower Drava showed slight organic pollution with high concentrations of dissolved oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…Right side tributaries also have to be taken into consideration. According to Gvozdic et al [37], the lower Drava River showed slight organic pollution downstream of the city Osijek. Persic et al [38] are reporting only moderate signs of distortion, as a result of anthropogenic activities in watercourses draining the forested catchment of the Spacva River basin.…”
Section: Resultsmentioning
confidence: 99%
“…Right side tributaries also have to be taken into consideration. According to Gvozdic et al [37], the lower Drava River showed slight organic pollution downstream of the city Osijek. Persic et al [38] are reporting only moderate signs of distortion, as a result of anthropogenic activities in watercourses draining the forested catchment of the Spacva River basin.…”
Section: Resultsmentioning
confidence: 99%
“…Amonijum jon nije toksičan za žive organizme. Međutim, opasnost za živi svet postoji u slučaju većih vrednosti pH (iznad 9) kada je dominantan NH 3 kao toksična komponenta [12,13].…”
Section: Uticaj Rudarskih Aktivnosti Na žIvotnu Sredinuunclassified
“…Povećane vrednosti su uglavnom posledica ispuš-tanja komunalnih i industrijskih otpadnih voda i primena nitratnh đubriva. Nezagađene vode uglavnom sadrže manje od 0,1 mg NH 4 -N, a veće vrednosti mogu da budu posledica ispuštanja komunalnih otpadnih voda [17,18].…”
Section: Prvoj Grupi Pripadaju Merne Stanice Krivaje (Mali Iđoš I Srbunclassified
“…Temperatura može uticati na hemijske i biološke procese i samim tim na uslove života akvatičnih organizama. Na osnovu navedenih podataka može se zaključiti da su temperature vode na mernim stanicama uslovljene sezonskim varijacijama [17][18][19].…”
Section: Prvoj Grupi Pripadaju Merne Stanice Krivaje (Mali Iđoš I Srbunclassified